NILAI EKONOMI AIR UNTUK RUMAH TANGGA DAN KERAMBA DI SEKSI PENGELOLAAN TAMAN NASIONAL (SPTN) WILAYAH II SEMITAU TAMAN NASIONAL DANAU SENTARUM (TNDS) KABUPATEN KAPUAS HULU - Anggraeni, Septia; Hardiansyah, Gusti; Natalina, Uke (Universitas Tanjungpura, 2013)
Forest benefits especially in national park such as recreation facilities, watersheds, protection of ecological proces, biodiversity, education and research as well as the future of collateral value is valued lower because still many people who dont understand the value of the various benefits of Forest Resources especially the benefits of water. To understand the benefits of Forest Resources will require an assessment of all the resulting benefits.The research objectives are to examine the influence of socioeconomic factors on domestic water and fish cages consumption, calculate the economic value of water for domestic and fish cages as well as examine the contribution of the use of water to communities in the TNDS SPTN Region II Semitau. The method used is descriptive method through a survey form and interview techniques both unstructured and structured observations and direct measurements in the field. Analysis using the method of determination of the demand model